Ժողովրդավարական արժեհամակարգի պաշտպանության հիմնախնդիրը արտաքին ագրեսիայի պայմաններում - Սիմոնյան, Գուրգեն (Լիմուշ հրատ.)
No state in the world exists solely for the sake of today. Even the prosperous present of the modern developed countries is the embodiment of the strategy of the distant and recent past, the achievement of which was made possible through a sequence of tactical decisions, continuously fighting against external and internal challenges that threaten their identity, political and legal system, as well as their political culture. By building a strategic future, the state implements its, perhaps, most basic function: ensuring the transition of the titular nation into the future while simultaneously ensuring the continuity of national identity and sovereignty. To implement the above policies, the state adapts its strategy in accordance with two realities - natural (peace) and crisis (war).
Keywords: Քաղաքագիտություն